The Impact of Caring for Children with Special Needs on Maternal Subjective Well-being: A Bibliometric Analysis - Alice Zellawati; Sugiharto; Mulawarman; Sunawan (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The literature on Maternal Subjective Well-being (MSW) has grown rapidly over the past two decades. MSW is a multidimensional construct encompassing subjective evaluations of mothers’ lives, including overall life satisfaction, happiness, and emotional well-being. Method: A systematic literature review was conducted using PubMed, Scopus, and Google Scholar databases to identify English-language articles published between 2013 and 2023 using the keywords mother, subjective well-being, and special needs children, yielding 2,200 records, of which 8 met the inclusion criteria and were subsequently analyzed using the PRISMA framework and thematic synthesis approach. Results: The review identified eight eligible studies and found that maternal subjective well-being is influenced by both internal factors (self-efficacy, hope, positive perceptions, and resilience) and external factors (social support, family functioning, and partner relationships). The findings highlight that strengthening psychological resources and social support systems may play a key role in improving the well-being of mothers caring for children with special needs. Novelty: The review highlights resilience as a key protective factor that can mitigate the negative effects of parenting stress on maternal subjective well-being and quality of life among mothers of children with disabilities. A notable research gap is the limited understanding of how protective factors, particularly resilience and benefit finding, can be developed and activated to support positive maternal adaptation to caregiving demands.